Purification and characterization of an agglutinin from datura innoxia with antineoplastic activity - Singh, Ruby; Nawale, Laxman; Gaikwad, Sushama M.; Suresha, C. G. (National Science Day, At CSIR-NCL, 2015)
Lectins are carbohydrate binding proteins of non-immune origin. Due to their multivalency, lectins can be easily detected using agglutination. Lectins are reported to induce cytotoxicity or inhibition of growth in various cancer cells., hence good therapeutic startegy against cancer. Factors such as specificity, stability, assay rapidity, and costs combine to make lectins attractive diagnostic reagents. Datura innoxia belongs to family of Solanaceae.All parts of the plant are hallucinogenic, hypnotic and narcotic. Application: at low dose acts as pain killer, relieves asthma and rheumatism.

Two chitotriose-specific lectins show anti-angiogenesis, induces caspase-9-mediated apoptosis and early arrest of pancreatic tumor cell cycle - Singh, Ruby; Nawale, Laxman; Sarkar, Dhiman; Suresh, C. G. (Plos One, 2016)
The antiproliferative activity of two chito-specific agglutinins purified from Benincasa hispida (BhL) and Datura innoxia (DiL9) of different plant family origin was investigated on various cancer cell lines. Both lectins showed chitotriose specificity, by inhibiting lectin hemagglutinating activity. On further studies, it was revealed that these agglutinins caused remarkable concentration-dependent antiproliferative effect on human pancreatic cancerous cells but not on the normal human umbilical vein endothelial cells even at higher doses determined using MTT assay. The GI(50) values were approximately 8.4 mu g ml(-1) (0.247 mu M) and 142 mu g ml(-1) (14.8 mu M) for BhL and DiL9, respectively, against PANC-1 cells. The growth inhibitory effect of these lectins on pancreatic cancer cells were shown to be a consequence of lectin cell surface binding and triggering G(0)/G(1) arrest, mitochondrial membrane depolarization, sustained increase of the intracellular calcium release and the apoptotic signal is amplified by activation of caspases executing cell death. Interestingly, these lectins also showed anti-angiogenic activity by disrupting the endothelial tubulogenesis. Therefore, we report for the first time two chito-specific lectins specifically binding to tumor glycans; they can be considered to be a class of molecules with antitumor activity against pancreatic cancer cells mediated through caspase dependent mitochondrial apoptotic pathway.